Study on the documents of Java in Siku Quanshu; Historical knowledge and historians' point of view - Wuryandari, Nurni Wahyu (Wacana, Journal of the Humanities of Indonesia, 2014)
The dissertation discusses various documents on Java collected in Siku Quanshu (Complete Library of Four Treasures). The documents used as the sources of this study are the ones with complete pictures and strong narration on Javanese recorded from Han Dynasty (206 bc-220 ad) to Ming Dynasty (1364-1644) in order to reveal what kind of historical knowledge or historical information is delivered by Chinese historians in general and what kind of point of view is used by historians to deliver the notes about Java. Through analytical reading, the readers will find that historians paid attention to three issues: the relationship between China and Java, the condition of Javanese kingdoms and their culture, and the Java land natural resources. People of China regard their country as an ancient country with long history of remarkable civilization which located in the centre of the world. The awareness of how important is their country, indirectly influences the historians' points of views. The texts analyzed indirectly prove that some areas on Java are culturally left behind and the countries beyond China, including Java, are the barbaric ones obliging their people to submit or pay tributes to the Kingdoms of China.